(3Odjd EYOGO hJbjje OQGSGJ GdLOhi ddeTQhYGJ GdUfGYjIs - (3eMeO gTGe(B, (3NhGLcjIs ((3YeGf(B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY(B,s, 2004)
(3eQGMd OhQI GdeTQhY(B- (3OQGSI GdLOhi GdEbJUGOjI hGdafjI(B- (3OQGSI GdLOhi GdEbJUGOjI hGdafjI(B.s
Keywords: (3GdLOhi GdEbJUGOjIs; (3GdeTGQjY GdEbJUGOjIs; (3GdeTQhYGJ GdUfGYjIs; (3OQGSGJ GdLOhis